2016
DOI: 10.21608/jppp.2016.50071
|View full text |Cite
|
Sign up to set email alerts
|

THE RELATIONSHIP BETWEEN PLANTING DATES AND SOME CLIMATIC FACTORS ON THE INFESTATION OF EGGPLANT CULTIVARS WITH THE TWO-SPOTTED SPIDER MITE, Tetranychus urticae KOCH.

Abstract: Field studies were carried out at the Experimental Farm, Faculty of Agriculture, Assiut University, during two successive seasons of 2014 and 2015 used three planting dates (early summer, summer and nili plantations) in order to study the relationship between planting dates as well as some of the climatic factors (temperatures and relative humidity) on the census of the twospotted spider mite, Tetranychus urticae Koch on some eggplant cultivars (i.e., black balady, white balady and romy). The results obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Acarological studies which were carried out in Egypt revealed that spider mites particularly T. urticae may cause remarkable damage to infested different solenaceous crops (El-Saiedy et al, 2015;Abou El-Saad, 2016;Abou Ouf, 2016;Ali et al, 2017). Studies have been conducted in different countries to assess the effect and potential of natural enemies for controlling this pest.…”
Section: Plant Protection and Pathology Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Acarological studies which were carried out in Egypt revealed that spider mites particularly T. urticae may cause remarkable damage to infested different solenaceous crops (El-Saiedy et al, 2015;Abou El-Saad, 2016;Abou Ouf, 2016;Ali et al, 2017). Studies have been conducted in different countries to assess the effect and potential of natural enemies for controlling this pest.…”
Section: Plant Protection and Pathology Researchmentioning
confidence: 99%
“…In 2014, the total areas cultivated with eggplant in Egypt reached 49713 hectares produced approximately 1257913 tons (FAO, 2014). Many authors cleared that one of the factors contributing to low yields is injury caused by many arthropod pests, particularly phytophagous mites that are widely spread during the growing season of eggplant (Adango et al, 2006;Ohno et al, 2012;Azandeme et al, 2015;Abou El-Saad, 2016). Among the http:/www.journals.zu.edu.eg/journalDisplay.aspx?Journalld=1&queryType=Master…”
Section: Introductionmentioning
confidence: 99%